Mechanism of boron incorporation into calcites and associated isotope fractionation in a steady-state carbonate-seawater system. (November 2018) - Wang, Yi-Jing; Wei, Hai-Zhen; Jiang, Shao-Yong; van de Ven, Theo G.M.; Ling, Bao-Ping; Li, Yin-Chuan; Lin, Yi-Bo; Guo, Qi
Abstract: An investigation on the interface reactions and boron isotope fractionation in a steady-state carbonate-seawater system was performed to better understand boron incorporation into CaCO3 in a natural environment. In seawater, inorganic carbonate crystals did not precipitate even when the solution reached saturation and the presence of carbonic anhydrase enzyme promotes the process, indicating the precipitation kinetics of inorganic carbonates from natural seawater is fairly slow. Both theoretical and experimental evidence proved that boron incorporation into calcite might be defined as an adsorption-precipitation process rather than a substitution of CO3 2− by HBO3 2− in the crystal lattice, where the charged B(OH)4 - ions adsorb preferentially over H3 BO3 onto positively charged calcite crystal surfaces and finally co-precipitate into occlusions or inclusions after new layers of calcites formed. The Langmuir isotherm well describes the adsorption process, yielding a maximum adsorption capacity [B]solid-max of 0.33 ± 0.04 mg⋅g −1 and an equilibrium constant K of 0.0053 ± 0.0003. Langmuir kinetics also describes previous studies with [B]solid-max of 71.4–418 μg⋅g −1 for calcite and aragonite, covering the variation of boron contents in a variety of biogenic carbonates. The boron isotope fractionations in ulexite-seawater and calcite-seawater systems are distinct. In the former one the fractionation factor (αulexite-seawater = 0.995 ± 0.001) suggests that both trigonal and tetrahedral species of boron enter into ulexite crystals via rapid precipitation, and in the latter one (α4-3 = 0.9736 ± 0.004) confirms that only the charged B(OH)4 - species interacts with the crystal surface in calcite. Graphical abstract: Highlights: Boron isotope fractionations in ulexite-seawater and calcite-seawater systems are distinct. Boron uptake by carbonates might be defined as an adsorption-coprecipitation mechanism. The adsorption process follows the Langmuir isotherm. Both Mg/Ca and Sr/Ca variations in calcium carbonate respond to the solution chemistry.